Regulation of Private Recruitment Agencies in Morocco: An Institutional and Legal Analysis of the Existing Framework - KHAIR, Abdelhamid; BELMOUFFEQ, BOUCHRA (Revue Internationale du Chercheur, 2025)
Abstract This article provides an in-depth analysis of the regulatory framework governing Private Employment Providers (PEPs), legally designated as Private Recruitment Agencies (PRAs) in Morocco. Drawing on neo-institutional theory, it explores the mechanisms of institutional isomorphism (coercive, normative, and mimetic) that shape how PRAs structure themselves and comply with regulatory standards. The research adopts a qualitative and documentary approach based on legal texts, institutional reports, academic literature, and field-based data. The study offers a detailed overview of Morocco's private employment intermediation market, highlighting the gaps between the legal framework (notably the Moroccan Labor Code and ILO Convention No. 181) and actual practices. It identifies major barriers to formalization, including legal ambiguities (especially between PRAs and temporary work agencies), financial and administrative burdens, and weak social protection for temporary workers. The article concludes with actionable recommendations to improve legal clarity, ease operational constraints, and strengthen enforcement mechanisms. It also outlines future research avenues focused on digital regulation tools, managerial adaptation strategies, and territorial dynamics in the organization of PRAs